Current Status and Influencing Factors of Secondary Traumatic Stress in Emergency and Intensive Care nurses:A Cross-Sectional Analysis - Yao J; Zhou X; Xu D; Liu T; Gui Y; Huang Y (Psychology Research and Behavior Management, 2024)
Jiapei Yao,1,2 Xindie Zhou,1,3 Dongmei Xu,1 Ting Liu,1 Yuanyuan Gui,4 Yong Huang1,3 1Department of Orthopedics, The Affiliated Changzhou Second People’s Hospital of Nanjing Medical University, Changzhou, People’s Republic of China; 2Hunan Normal University, Changsha, People’s Republic of China; 3Changzhou Medical Center, Nanjing Medical University, Changzhou, People’s Republic of China; 4Department of Psychogeriatric Intensive Care Medicine, Xianlin Campus, Tongde Hospital of Zhejiang Province, Hangzhou, People’s Republic of ChinaCorrespondence: Yuanyuan Gui; Yong Huang, Email Guiyuanyuansltd@163.com; huangyong@njmu.edu.cnObjective: Secondary traumatic stress (STS) is stress caused by helping or wanting to help someone who has suffered a traumatic event. STS has adverse effects on nurses and their work, such as reduced career achievement, an increased staff turnover rate, inability to complete work, avoidance of contact with patients, mental exhaustion, negative emotions which seriously affect the quality of their work and life. The study to investigate secondary traumatic stress in emergency and intensive care nurses and analyze factors that influence it.Material and Methods: The study was a cross-sectional survey. Convenience sampling was used to select hospital emergency and intensive care department nurses (n=434) who met the inclusion and exclusion criteria from August to October 2021 to participate in this study. They provided demographic data and completed measures of secondary traumatic stress, emotional intelligence, anxiety and depression. Data analysis included independent samples t-tests, one-way analysis of variance, Pearson correlation analysis and multiple linear regression analysis.Results: Almost one-third (30.7%) of participants were at moderate risk for Secondary Traumatic Stress Scale or above, with high average scores on measures of anxiety (GAD-7 average = 6.05 ± 4.13), and depression (PHQ-9 average = 6.35 ± 4.85). The results of multiple linear regression analysis showed that the average daily amount of sleep in the past week, the number of night shifts in the past month, emotional intelligence, anxiety, and depression influenced secondary traumatic stress, explaining 70.8% of the variance.Conclusion: The STS of emergency and intensive care nurses in Changzhou is at a high level. Sleep time, number of night shifts and emotional intelligence are related to secondary traumatic stress and anxiety and depression significantly predicted the degree of secondary traumatic stress. Nurses need to master effective treatment methods for secondary traumatic stress, to improve their work efficiency and nursing quality and ensure nursing safety.Keywords: secondary traumatic stress, emergency and intensive care department nurses, anxiety, depression, emotional intelligence